ASSESSMENT OF RADIOACTIVITY AND RADIOLOGICAL HAZARD FROM NATURAL RADIONUCLIDES CONTAINED IN RICE FROM NORTH MACEDONIA - Angeleska, Aleksandra; CHrcheva - nikolovska, Radmila; Dimitrieska Stojkovikj, Elizabeta; Esmerov, Igor; Jovanov, Stefan; Angelovski, Ljupcho; Uzunov, Risto (Faculty of Agriculture, University of East Sarajevo, Republic of Srpska, Bosnia and Herzegovina..., 2025)
Studies on radioactivity in consumable food are becoming increasingly important from a safety perspective as it is necessary to estimate the dose of ingestion by the public. For this reason, the focus of this study was on determining the activity concentrations of 226Ra, 232Th, and 40K. Thirty-eight rice samples were collected during 2024 from rice fields (city of Kochani) in the Republic of North Macedonia and the samples were analyzed by using a high-purity germanium (HPGe) detector for assessment of natural and artificial radioactivity. The average activity concentrations of 226Ra, 232Th, and 40K of the tested samples were 2.17±0.70, 1.78±0.72, and 48.48±1.92 Bq/kg, respectively. No artificial radionuclide was found in any of these samples. The total absorbed dose (D) was 4.10 D (nGy h-1), while the average value of the radium equivalent activity in all samples was 8.10 Bq kg-1, which was less than the maximum permitted value of 370 Bq kg-1. The values of Hex, Hin and 𝐼γ for the samples were 0.02, 0.027 and 0.064, which are less than one in all samples indicating the harmlessness of the samples. The average activity concentrations of 226Ra, 40K, and 232Th (Bq kg-1) in the samples were used to calculate the annual effective dose equivalent (AEDE), whose average value for all samples was 0.005(μSv/y). The average calculated cancer risk due to the intake of the tested radionuclides found in the rice samples was estimated at 0.017, which is within the range of acceptable risk values recommended by USEPA. The results of this study indicate that the intake of radionuclides due to consumption of the mentioned food does not have a harmful effect on public health. These data would be useful for establishing a baseline for the concentrations of natural radioactivity in food products consumed in the Republic of North Macedonia.
Keywords: gamma spectrometry, radiation risk, rice, cancer risk